Air Flow Distribution Analysis By Using CFD Simulation - Mohamed Yusop, Fatimah; Ramli, Sakira (Progress in Engineering Application and Technology, 2020)
A modern building has requirements need to consider to increase the quality of the building. In design the building, fresh air, cooling and heating is the important role to consider. The Heating,Ventilation and Air conditioning (HVAC) is most important part in building. Centralized system is the common use especially in large building. Usually, the system are using diffuser for air inlet and grille for air return. Therefore, the aim of this study is to determine the effectiveness of diffusers and grilles position in order to distribute the cool air into building. The objectives of this study are to perform a simulation in building and validate the simulation data with actual data. The CAD model was developed by using SolidWorks software. Then, the simulation was performed by using ANSYS-FLUENT softaware. The simulation result was validated by compare actual data. The result of temperature of air velocity of the room is not acceptable according to MS:1525:2014. The minimum velocity of the simulation data is 0.001m/s and the temperature is 17°C and the maximum velocity is 3.5m/s and the temperature is 18.5°C.The difference velocity of actual data and simulation for maximum and minimum velocity is 29.9% and 99.5% and for the maximum and minimum temperature difference is 0.53% and 4.2%. The minimum air velocity that acceptable for room air velocity based on Ms:1525:2014 is 0.15 m/s and the temperature is 23°C. Therefore, the improvement of HVAC design is required.